Internal Clock Drift Estimation in Computer Clusters. (14th May 2008) - Marouani Marouani, Hicham Hicham; Dagenais Dagenais, Michel R. Michel R.
Abstract : Most computers have several high-resolution timing sources, from the programmable interrupt timer to the cycle counter. Yet, even at a precision of one cycle in ten millions, clocks may drift significantly in a single second at a clock frequency of several GHz. When tracing the low-level system events in computer clusters, such as packet sending or reception, each computer system records its own events using an internal clock. In order to properly understand the global system behavior and performance, as reported by the events recorded on each computer, it is important to estimate precisely the clock differences and drift between the different computers in the system. This article studies the clock precision and stability of several computer systems, with different architectures. It also studies the typical network delay characteristics, since time synchronization algorithms rely on the exchange of network packets and are dependent on the symmetry of the delays. A very precise clock, based on the atomic time provided by the GPS satellite network, was used as a reference to measure clock drifts and network delays. The results obtained are of immediate use to all applications which depend on computer clocks or network time synchronization accuracy.